Acute systemic complications of intravitreal bevacizumab and triamcinolone injections – a comparative study - Mohammad Karim Johari (Folia Medica, 2022)
Introduction: Macular edema is a common visual threatening complication in patients with diabetic retinopathy and retinal vein occlusion. The injection of intravitreal drugs, such as anti-vascular endothelial growth factor (anti-VEGF) and corticosteroids, revolutionized the treatment of these diseases. Aim: To compare and assess the acute systemic complications of intravitreal bevacizumab and triamcinolone injections in patients with diabetic retinopathy and retinal vein occlusion. Materials and methods: The study population included 211 patients with diabetic retinopathy and retinal vein occlusion who required intravitreal injections of bevacizumab and triamcinolone. In this study, 118 patients had generally received intravitreal injections with bevacizumab and the rest (93 patients) injections with triamcinolone. Experimental data, including demographic information, number of injections, the history of comorbidities, intraocular pressure, and systemic hypertension before and after injections, were recorded on specific forms following groups’ classification. In addition, the incidence of various complications was investigated during one month after the intravitreal injections. Results: In the present study, we included 211 patients (mean age 62.41±11.34 years, median - 63 years). The results showed that there was no significant correlation between the injectable drug and changes in increased intraocular pressure (IOP) (p=0.66). No significant difference was detected for systemic hypertension in any of the studied groups. On the other hand, the incidence of complications of blood sugar, facial skin redness, neurological problems of TIA and CVA, myocardial infarction, vascular problems after injection, and ocular complications were estimated to be zero, 1.4, 0, 0.8, 0, and 6.1%, respectively. Conclusions: Overall, the results indicated a prevalence of 1.4% for systemic complications and a prevalence of 6.1% for ocular complications. Accordingly, it seems that intravitreal injections of both drugs studied in the present study are placed in the group of low complication medications.